Long Segment Lumbosacral Fusions in Obese Patients. (16th November 2020) - Baum, Justin; Hatef, Jeffrey; McGahan, Benjamin; Viljoen, Stephanus; Grossbach, Andrew J; Farhadi, Francis
Abstract: INTRODUCTION: Long segment lumbosacral spinal fusions are a common treatment modality for patients diagnosed with spinal deformity. Complication rates and fusion rates regarding obese patients undergoing these surgeries is not well defined. METHODS: A retrospective chart review was performed on patients undergoing long segment lumbosacral fusion from at least L3 to sacrum that also had pelvic fixation placed (either S2AI or iliac bolt) from 2017–2019. Baseline demographic data, operative time and blood loss, fluoroscopy time, postoperative complications, lumbar lordosis, and implant failure rates were recorded. Patients with BMI greater than 30 were compared to patients with a BMI less than 30. RESULTS: There were 184 patients identified. 94 patients met criteria for obesity (51%). Smoking rates were 23% and not significantly different between the two groups. Postoperative complication rates were 45% and not different between the two groups. The most common complication was ileus (11% of patients). Implant failures (15%) and reoperations (15%) were not significantly different. Preoperative lumbar lordosis was higher in obese patients (40.6 degrees obese patients, 32.1 degrees non-obese patients, P  = .039). Postoperative change in lordosis was less in obese patients than non-obese patients (9 degrees obese patients, 16 degrees non-obese patients, P  = .006). CONCLUSION: Long segment lumbosacral fusions with pelvic fixation are extensive and challenging cases with high complication rates. Obese patients in our cohort do not have higher complication rates, implant failures, or reoperation rates. Patients should not be ruled out for surgical treatment on BMI alone.